Setting the Age Limit for Marriage in India and Pakistan - Muntasir; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2024)
The reform of the age limit of marriage in various countries through the codification of family law in the marriage legislation seems to be a relevant and urgent solution. This article will analyze first: how is the age limit of marriage in the legal system of India and Pakistan? second: how does the age limit of marriage affect the people of India and Pakistan? using a qualitative descriptive method. The data is collected through the study of various relevant references. The results of this study provide conclusions, first, in the Indian legal system regulates the age of marriage through the Child Marriage Restraint Act of 1929 revised by The Prohibition of Child Marriage Act of 2006 which sets the legal age for marriage at 18 years for women and 21 years for men, while in Pakistan through Law Number 29 of 1929 which has been amended through Ordinance Number 8 of 1961 sets the age limit for men at 18 years for men and 16 years for women. The age of marriage is different in the two countries because the determination of the standard age of marriage depends on the view of Islamic law adopted and used as a guide by the State. Both the Indian and Pakistani Marriage Acts specifically prohibit underage marriages, but there are still obstacles that prevent the full implementation of these regulations because the sanctions imposed are only considered as an additional cost of getting married and there are strong cultural or customary factors. Therefore, it takes a firm policy from law enforcement and awareness from the community itself to maintain the smooth implementation of this law.